The Impact of Firm Size and Leverage on Profit Quality: An Empirical Review of Family Ownership - Rizal, Noviansyah; Chandrarin, Grahita; Assih, Prihat (Indonesian Journal of Advanced Research, 2024)
This research aims to analyze the influence of firm size and leverage on earnings quality and the moderation of family ownership on the influence of leverage and firm size on earnings quality. The research population includes all manufacturing companies listed on the Indonesia Stock Exchange for 2019-2022. The sampling technique uses purposive sampling, so the sample must meet the specified criteria to represent the population. Thus, the number of samples in the research was 664 companies. The data analysis method uses descriptive and Moderated Regression Analysis (MRA). The research results show that firm size positively affects earnings quality, leverage does not affect earnings quality, and family ownership proves a positive interaction between firm size and earnings quality. Family ownership positively interacts leverage with earnings quality, meaning that leverage in family-controlled companies can encourage management to carry out discretionary accruals. This research contributes positively to companies by providing information about the factors that influence earnings quality, gaining knowledge about quality earnings through the influence of firm size and leverage, and highlighting the moderating potential of family ownership in this context. The practical implications can help company stakeholders optimize earnings management policies and strategies.